Edukasi Program Latihan Fisioterapi Pada Penderita Stroke Di Posyandu Lansia Desa Sanggung - Taufik Eko Susilo; Ni'mah Hastuti; Anggitya Widyastuti; Rosalia Putri Hidayat; Indy Viorohma Asinta Zahra; Lintang Ayininggar; Arif Pristianto (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
One of the health problems is stroke. Stroke is a disease affecting the body's movement and functional systems which is the main factor in neurological disorders. Stroke is the second highest cause of death and the third leading cause of disability at world level. Stroke can affect the whole body such as paralysis, impaired cognitive function, difficulty speaking, emotional difficulties, pain and problems in daily life activities. Posyandu Ngudi Saras is one of the posyandu for the elderly in Sanggung Village. There is a shortage of physiotherapists in this place, which is one of the obstacles faced by residents in Sanggung Village. Apart from that, there is a lack of education about physiotherapy exercise programs, especially for stroke sufferers. This can be seen from the patient not continuing the exercise program at home so that his condition worsens and when carrying out activities he depends on other people. Based on these problems, we offer a solution by providing education about physiotherapy exercise programs from sitting to standing and from standing to walking to patients and families. This physiotherapy exercise program is useful for increasing the patient's independence in carrying out activities, especially when walking and standing. Activities are carried out door to door in the homes of stroke sufferers and with an interpersonal approach. Community service through this form of educational activity has been carried out and can increase the knowledge of stroke sufferers and their families.